Genital tract fistula: Changing trends in presentation and outcome - Ojen, AO; Abduls-Salam, RA; Morhason-Bello, IO; Bello, OO; Lawal, OO (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To find out the clinical profile of obstetric fistula. Methods: A retrospective review of women presenting for OF repair in Ibadan, Oyo State from 2017-2018. All repairs were performed by the Oyo State fistula team at Adeoyo Maternity Hospital or University College Hospital, Ibadan. Two hundred and eighteen women were repaired during the period; information on socio-demographic and presentation characteristics was extracted. Data analysis was done using IBM SPSS version 25.0. Results: The commonest cause of genital tract fistula in this review was obstructed labour (68.5%), 44.9% of the women had caesarean delivery either to relieve obstruction or as elective procedure. Only 8.3% had elective caesarean section and 5.6% had gynaecologic surgery. Majority were urinary fistula (92.5%) and in the mid-vaginal (21.6%) location followed by juxta-cervical and ureterovaginal fistula (9.2%). Urethral involvement and severe vaginal fibrosis were seen in 12.4% and 61.3% of cases respectively. Conclusions: There is a need for continuing medical education on critical emergency obstetric care skills in order to improve maternal health care service delivery.